Assessing genetic diversity of Dalbergia stevensonii: an endangered species in Guatemala - Ruiz Chután, José Alejandro; Maňourová, Anna; Degu, Hewan Demissie; Berdúo-Sandoval, Julio Ernesto; Kalousová, Marie; Barrios, Sara; Villanueva-González, Carlos Enrique; Herrera, Myrna; Lojka, Bohdan (BOSQUE, 2024)
Owing to extensive overexploitation and continuous habitat loss in recent decades, Dalbergia stevensonii has become endangered in Central America and its place of origin. Genetic diversity is essential for ensuring the long-term survival of the species and is vital in breeding programs. However, knowledge of the genetic diversity of D. stevensonii is limited, as no study has been conducted to estimate the population variability in Guatemala. This study is the first to determine the genetic diversity and structure of wild populations of D. stevensonii in Guatemala using molecular markers. The genetic diversity of 90 wild D. stevensonii trees from six populations located in their natural range is currently being evaluated. Genetic diversity was moderate, with an average of 5.83 alleles per locus, a mean Shannon index value of 1.42, and observed and expected heterozygosity of 0.32 and 0.37, respectively. AMOVA indicated that only 6 % of the genetic variation was between populations, and genetic distance values (pairwise FST) suggested moderate differentiation between populations. STRUCTURE and DAPC analyses revealed the existence of three clusters for the 90 samples, while the genetic differentiation among populations is attributed more to genetics than to geographic distance. Conservation of the genetic diversity of D. stevensonii is critical to ensure its long-term survival, and the success of breeding programs focused on improving the traits and characteristics of the species, such as growth rate, wood quality, and resistance to pests and diseases. These findings provide a crucial genetic basis for conservation, management, and restoration of this endemic species.